Cécile and Oskar Vogt: their life, work, and contribution to epileptology Cécile & Oskar Vogt: Leben, Werk und ihr Beitrag zur Epileptologie - Kasper, Burkhard S. (Clinical Epileptology, 2025)
Cécile and Oskar Vogt were brain researchers who systematically investigated the structure and function of the central nervous system together over decades. At the turn of the century in Berlin, even before 1900, they started their cytoarchitectonic and myeloarchitectonic studies using whole brain sections and began performing cortical stimulation experiments in different species, which they continued until their death. With the restricted resources of a private Berlin flat, they started their “Neurology Central Station,” which became the university neurology laboratory in 1902 and the Kaiser Wilhelm Institute (KWI) for brain research in 1914. As late as 1931, they moved into a newly built modern KWI at Buch in Berlin. This KWI represented the first institute of its kind worldwide, made possible by generous support from the Krupp family and the Rockefeller Foundation. Removed from the Berlin institute by the Nazi regime, they built a new institute in the black forest. Their legacy today is saved and continued by the Cécile and Oskar Vogt Institute for Brain Research in Düsseldorf, Germany. As part of the Vogt group, Korbinian Brodmann developed his famous cytoarchitectonic map. They discussed their cortical stimulation results and compared them to those of Otfrid Foerster and Wilder Penfield, among others. The Vogts worked on abundant topics. Although they did not study epilepsy explicitly, Ammon’s horn sclerosis (AHS) represented a central lesion in their work, for the Vogts observed “selective vulnerability of brain regions” and explained this by their theory of pathoclisis. Selective vulnerability was discussed controversially for AHS in epilepsy, but turned out to be quite correct, although the Vogts were not able to prove their concept given the methods of the time. Many of Cécile and Oskar Vogt’s results still have an impact today and represent an important fundament of modern epileptology.
CRIS-Team Scopus Importer:2025-05-09
Keywords: Architectonic; Cécile Vogt; History of epileptology; Oskar Vogt; Pathoclisis